Comment on “Population Pharmacokinetics of Total and Unbound Isavuconazole in Critically Ill Patients: Implications for Adaptive Dosing Strategies” and “High Variability in Isavuconazole Unbound Fraction in Clinical Practice: A Call to Reconsider Pharmacokinetic/Pharmacodynamic Targets and Breakpoints” - Kong, Leping; Alffenaar, Jan-Willem C.; Stocker, Sophie L. (Clinical pharmacokinetics, 2024)
Currently, there is no evidence that unbound isavuconazole concentrations are a better predictor of treatment response than total concentrations. [...]clinical implementation of monitoring unbound isavuconazole concentrations in routine clinical practice is difficult to justify. While isavuconazole is highly protein bound, it has a low intrinsic clearance; therefore, changes in the fraction unbound are unlikely to impact its pharmacokinetics (specifically clearance). [...]we propose that the importance of measuring unbound isavuconazole concentrations, as a better predictor of treatment response, should be established before implementation of routine monitoring of free concentrations. [...]a better understanding of isavuconazole pharmacokinetics/pharmacodynamics and its unbound drug concentrations will have practical implications regarding how we perform therapeutic drug monitoring.